PENGARUH PENYARUNGAN DENGAN BERBAGAI KETEBALAN PLASTIK DAN DIAMETER BUAH TERHADAP SERANGAN PENGGEREK BUAH KAKAO Conopomorha cramerella (Snellen) (LEPIDOPTERA : GRACILLARIDAE) - NI MADE DELLY RESIANI (AGRICA, 2014)
This research is aimed to find out the preference of cocoa pod borer to diameter, biophysical, and biochemistry cocoa pod; the percentage of infested pods, percentage of seed damaged, and percentage of yield lost. In addition, this research is also aimed to assess the effect of plastic thickness on cacao pod rot disease, the effect of sheathing on the black ant and mealybug populations on pods. This research was conducted at Selemadeg District, Tabanan Regency from October 2009 until January 2010. The field trial was arranged into randomized complete block design (RCBD) by 15 treatments were sheathing with various thickness of plastics (S0-S4) and cocoa pod diameters (B1-B3). The results indicated that, based on the percentage of the infested pod, cocoa pod borer has preferred the fruit with diameter > 4.5-7.5 cm. This condition may be contrasted, the smallest pod size (3,5-4,5 cm) was the healthiest pod, even though it contains more nutritionally compound. The smaller pod rot disease in red and green types. Sheathing by plastic of > 0.02 mm thick in medium size of pods was the most effective to prevent cocoa pod borer infestation. Sheathing with plastic was not affecting the population of both black ants and mealy bugs. Based on these results, it can be suggested that sheathing with plastic of > 0.02 mm thick on medium size of the pod is promising control measure to prevent yield lost caused by cocoa pod borer and cocoa pot rot disease.